2015
DOI: 10.15376/biores.10.1.1330-1345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar Application on the Efficacy of the Nitrification Inhibitor Dicyandiamide in Soils

Abstract: A series of laboratory incubation experiments was conducted to evaluate the effect of biochar application on the efficacy of the nitrification inhibitor (NI) dicyandiamide (DCD) in Cambisol (pH 7.14) and Latosol (pH 4.83). The feedstocks (eucalyptus wood, coconut coir, and rice straw), pyrolysis temperatures (350, 500, and 650 ˚C), and application rates (0.5, 1.0, 2.5, and 5.0% of 200 g soil) were identified as influential factors. The results showed that biochar could significantly reduce the effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In a laboratory study, Shi et al . 79 described lower DCD nitrification inhibitory ability when applied in combination with biochar. Given that DMPP reduces N 2 O emissions by inhibiting the microbial nitrification pathway, and if biochar amendment has been proposed as a potential tool to also mitigate N 2 O emissions, the addition of DMPP to biochar amended soils was expected to be a further benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a laboratory study, Shi et al . 79 described lower DCD nitrification inhibitory ability when applied in combination with biochar. Given that DMPP reduces N 2 O emissions by inhibiting the microbial nitrification pathway, and if biochar amendment has been proposed as a potential tool to also mitigate N 2 O emissions, the addition of DMPP to biochar amended soils was expected to be a further benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Electrostatic attraction, polar and non-polar organic-attraction and ion-exchange to the carbonized phase of biochar, and surface sorption to the non-carbonized phase are some of the mechanisms involved in the interactions of biochar with organic and inorganic contaminants 80 , reducing the efficiency of DMPP. One hypothesis to explain this reduction of the DMPP efficiency is that, due to its varied surface functional groups, micro-porous structure and large specific surface area, biochar has a strong affinity and adsorption ability for organic substances 79 . Thus, the ability of biochar to reduce the efficiency of DMPP may be explained by means of an adsorption process, as also described for the reduction in the bioavailability of heavy metals and/or pesticides in soil when biochar was added 81,82 .…”
Section: Discussionmentioning
confidence: 99%
“…Opportunities exist to use biochar as a carrier for this nitrification inhibitor. However; biochar produced from eucalyptus wood with a large surface area (426.4 m 2 g -1 ) reduced the inhibitory effect of another nitrification inhibitor dicyandiamide (DCD) in a neutral Cambisol [76]. This work demonstrated that sorptive biochars were more efficient at reducing the efficacy of the nitrification inhibitor than less sorptive ones.…”
Section: Properties Of Biochar Which Alter N Cycling N 2 O and Co 2mentioning
confidence: 81%
“…Applying stabilized fertilizer has been demonstrated to be an effective agricultural management practice for N-fertilizer use, which reduces the loss of gas emission through prohibiting urea release and the nitrification process, increases the content of NH4 + -N available for plant uptake, and then influences the nitrogen turnover of soil (Shi et al 2015;Meng et al 2020). In addition to the effect on N-transformation, research also shows that N-fertilization affects the rate of soil organic carbon (SOC) decomposition through regulating extracellular enzyme activities (Jian et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to explore the relationship between the change of enzyme activity and C or N conversion. To date, most researchers have aimed at straw management and normal N fertilizer (Shi et al 2015;Sihi et al 2019), but few have focused on stabilized fertilizer with a new kind of inhibitors combination and rice straw. Hence, this study explored the impact of straw and stabilized fertilizer added on soil C and N turnover according to related enzymes and rice growth.…”
Section: Introductionmentioning
confidence: 99%